The Effectiveness of Using Picture Strategy in Improving Speaking Abilty At The Second Grade Of SMA Negeri 3 Pematangsiantar - Natanael Saragih; Efraim Jansius Gultom (Bilingual : Jurnal Pendidikan Bahasa Inggris, 2022)
This study was designed due to a consideration that English speaking is a difficult subject to be mastered by students and using a right teaching strategy is important to improve theirs peaking ability. The study explored how effective is using pictures strategy in improving student’s speaking ability at the second grade of SMA Negeri 3 Pematangsiantar. The study was conducted at SMA Negeri 3 Pematangsiantar involving 60 students in second grade (class XI-IA1 and XI-IA2). Using quantitative approach and a true experimental research design, the study collected the data through pre-test and post-test. The data analysis that tcount (47.114) > ttable (2,021) at the significance level α=0,05 with degrees of freedom (df)= 34, Ho is rejected and Ha is accepted. It means that the using Picture Strategy siginificantly in Improving Speaking Skill at the second grade of SMA Negeri 3 Pematangsiantar. This finding conform the previous research finding that using picture strategy can help students to improve student’s speaking ability. Nevertheless, there were some problems gained in using picture strategy. Many students could not apply grammar correctly when they speak by using the strategy. The students are difficult to understand English when their friends speak English using picture. They could not speak English fluently and concentrate in speaking English when the teacher used the strategy